Temporal-Based multimedia data management for web services environment - Farham Mohamed
Multimedia data management applications such as storage, access, manipulation, integration and presentation are different from normal data. Multimedia data needs a huge size of multimedia database and the complexity of its data structure affects access and processing time. The development of multimedia application systems must meet several criteria to reduce the constraints in managing multimedia data. Nowadays, Multimedia Data Management Systems (MOMS) have been developed into a network and distributed environment. The system can be accessed by multiple users or organizations. The situation creates complicated data sharing especially when the multimedia data is often involved with the update process. Thus, MOMS should use the element of time to monitor the transactions and changes of multimedia data. Managing data using time element have appeared in various fields such as in medical, finance, hotel reservation, weather monitoring and computing. The main purposes of time element are to determine when a record is stored and when a record is changed. In temporal database applications, the old records are not deleted during update operation for future retrieval and usage. Two elements of time used in temporal database are transaction time and valid time. Transaction time represents the time when a data is recorded into a database. Valid time represents the time data in a database becomes valid or true before the data is updated. This study aims to develop a new model of multimedia data management application using temporal database. The element of time is used to monitor every transaction and change(event) that happen without deleting previous records of multimedia data. Past, current and future records can be achieved accurately and efficiently in accordance with a specific time period. The model will be developed in a distributed environment for faster access and unlimited collaboration. Distributed environment such as web services will create wider and interactive multimedia data sharing.